Effects of PM2.5 exposure and air temperature on risk of cardiovascular disease: evidence from a prospective cohort study - Zhihang Zhang; Ran An; Haoyan Guo; Xuanru Yang (Frontiers in Public Health)
Background and aimsEvidence from extensive cohort studies about the individual and combined associations of air pollution and air temperature with cardiovascular disease (CVD) morbidity is limited. This study aimed to examine the long-term effects of PM2.5 exposure and air temperature on CVD based on a cohort study of middle-aged and older populations in China.MethodsA total of 9,316 non-CVD adults (≥40 years old) who joined the China Health and Retirement Longitudinal Study between 2011 and 2018 were included in our analysis. The two-year average PM2.5 concentration and air temperature of the city where participants lived were calculated. The Cox proportional hazards model was conducted to analyze the associations of PM2.5 exposure and air temperature with CVD morbidity.ResultsIn the multivariable-adjusted model, each 10 μg/m3 rise in 2-y PM2.5 concentration was associated with an increased risk of developing CVD (hazard ratio [HR]: 1.30; 95% confidence interval [CI]: 1.27–1.32). Compared with individuals in the bearable temperature group, those with low temperatures had a higher risk of CVD (HR: 1.77; 95% CI: 1.53–2.04). Stratified analyses found that cardiovascular metabolic risk factors could not change these associations. Compared with individuals in the low-level PM2.5 exposure and bearable temperature group, those in the high-level PM2.5 exposure and low-temperature group had a 7.08 times higher risk of CVD (95% CI: 5.55–9.03).ConclusionLong-term PM2.5 exposure and low air temperature are associated with a higher risk of CVD. Consequently, efforts to reduce air pollution and enhance protection against cold temperatures are vital for mitigating CVD risk.